The Dietary Approaches to Stop Hypertension (DASH)-Style Diet and an Alternative Mediterranean Diet are Differently Associated with Serum Inflammatory Markers in Female Adults. Issue 3 (September 2018) - Sakhaei, Roya; Shahvazi, Simin; Mozaffari-Khosravi, Hassan; Samadi, Morteza; Khatibi, Nasim; Nadjarzadeh, Azadeh; Zare, Fateme; Salehi-Abargouei, Amin
Background: Studies on the association between a priori dietary patterns and serum highly sensitive C-reactive protein (hs-CRP) have led to inconsistent results, and we are not aware of any study on interleukin 17A (IL-17A) as an inflammatory marker associated with autoimmune diseases. Objective: The present study aimed to investigate the association between Dietary Approaches to Stop Hypertension (DASH) and the Mediterranean dietary patterns with circulating hs-CRP and IL-17A levels. Methods: In this cross-sectional study, female teachers (aged 20-50 years) who lived in Yazd, Iran, were randomly selected from elementary, guidance, and high schools from September 2015 to February 2016. Anthropometric data, as well as general information and dietary food intakes, were gathered, and each participant gave 1 blood sample. Participants were categorized into tertiles based on the DASH and the Mediterranean diet calculated scores. The associations between the dietary patterns and serum hs-CRP and IL-17A levels were assessed in the crude and multivariable models. In total, 320 female teachers aged 40.38 (8.08) years were included. Results: The DASH diet was associated with lower serum hs-CRP levels in the crude ( P = .05) and the fully adjusted models ( P = .02), while it was not significantly associated with IL-17A levels. The participants with the highest adherence to the Mediterranean diet had significantly lower circulating IL-17A levels ( P = .04) even controlling for all confounders ( P = .02); however, there was not a significant relationship between this diet and hs-CRP levels. Conclusions: The DASH and the Mediterranean dietary patterns might be differently associated with inflammatory markers. Further prospective studies are recommended to confirm our results.